Developing successful business strategies : gaining the competitive advantage - Reider, Rob, 1940- (2014 digital library., 2015)
This book presents effective planning of business strategies and related budgeting concepts, and those activities necessary for the successful growth of the organization. The planning process is shown to be an integral function of developing management strategies for future growth and the gaining of competitive advantage in these fast moving times. Budgeting is presented as a logical outgrowth and an essential part of the planning process rather than an independent internal activity. The book emphasizes the principal factors that should be considered in planning and budgeting for the company, what management and operations personnel must know to better understand effective planning for the business, and what can be done to enhance the overall strategic and financial planning for the organization.